CLASSIFICATION SCHEMES OF TOPONYMS (Konferensiyalar | Conferences, 2024)
This article deals with the  one of the debatable issues in the branch of modern linguistics - the classification of toponyms and their types. There are various views of linguists regarding the classification of proper names, many of which are given in this article.